Identification of the Significant Genes Regulated by Estrogen Receptor in Estrogen Receptor-Positive Breast Cancer and Their Expression Pattern Changes When Tamoxifen or Fulvestrant Resistance Occurs - Cheng, Ran; Qi, Liqiang; Kong, Xiangyi; Wang, Zhongzhao; Fang, Yi; Wang, Jing (Frontiers in Genetics, 2020)
Breast cancer is the most frequent malignant tumor in women, and the estrogen receptor (ER) plays a vital role in the vast majority of breast cancers. The purpose of the present study was to identify the significant genes regulated by ER in ER-positive breast cancer and to explore their expression pattern changes when tamoxifen or fulvestrant resistance occurs. For this purpose, the gene expression profiles GSE11324, GSE27473, and GSE5840 from the GEO database were used, which contain gene expression data from MCF7 cells treated with estrogen, MCF7 cells with silencing of ER, and tamoxifen- and fulvestrant-resistant MCF7 cells treated with estrogen (17β-estradiol), respectively. Differentially expressed genes (DEGs) between the treatment group and negative control were identified and subjected to pathway enrichment and protein-protein interaction (PPI) analyses. There were 230 DEGs in common among the three datasets, including 160 genes positively regulated by ER and 70 genes negatively regulated by ER. DEGs mainly showed enrichment for pathways in cancer, progesterone-mediated oocyte maturation, RNA transport, glycerophospholipid metabolism, oocyte meiosis, platelet activation, and so on. PPI network and modular analysis selected three significant clusters containing 19 genes. A total of 44 genes were involved in KEGG pathway results or PPI modular analysis, and 16 of them were found to correlate with relapse-free survival in patients with ER+/HER2- breast cancer who had undergone endocrine therapies only. Some of the genes’ expression patterns were different among wild-type, tamoxifen-resistant, and fulvestrant-resistant MCF7 cells such as DDX18, ANAPC7, MAD2L1, RSL1D1, and CALCR, etc., indicating different resistance mechanisms and potential prognostic markers or therapeutic targets for fulvestrant- or tamoxifen-resistant breast cancer.